Analysis of the Properties of Spark Plasma Sintered Ti6al4v Matrix Composites Enhanced with Nitride Nanoparticles - Abe, J. O.; Popoola, O. M.; Popoola, A. P. I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Ti6Al4V alloy serves as an optimal lightweight structural material. However, its restricted hardness adversely impacts its abrasion resistance under high performance structural conditions, thereby hindering its extensive use in the aerospace industry. This study employed spark plasma sintering (SPS) to develop Ti6Al4V matrix composites reinforced with 1, 3, and 5 wt. % of three refractory nitride nanoparticles of h-BN, TiN, and AlN. The developed composites were analyzed for microstructure, phase composition, densification, microhardness, and potentiodynamic polarization using field-emission gun scanning electron microscopy, X-ray diffraction, the Archimedes' method, microindentation, and linear polarization investigations. The microstructure and phase analyses revealed marginal porosity and cracks, with no indications of detrimental intermetallic phases. It was observed that as reinforcement content increased, composite densities decreased from 98.4 to 97.4 %, 98.62 to 97.63 %, and 98.64 to 95.14 % for h-BN, TiN, AlN reinforcements, respectively. The microindentation test indicated that, relative to the unreinforced alloy (331.79 HV), hardness increased proportionally with reinforcement content. Interestingly, h-BN exhibits a range of 672.05 to 740.43 HV, TiN ranges from 427.18 to 491.06 HV, and AlN shows values from 441.25 to 504.68 HV. The composite with 3 wt. % AlN presented the best potentiodynamic polarization behaviour with a superior polarization resistance of 5246.2 Ω and a lowered corrosion rate of 0.14321 mm/year. Meanwhile, 5 wt. % AlN-reinforced composite showed the worst densification and potentiodynamic polarization behaviour with a relatively decreased polarization resistance of 219.13 Ω and a higher corrosion rate of 3.6935 mm/year. Additionally, among the developed composites, the 3 wt. % h-BN-reinforced composite exhibited optimal properties, showcasing a microhardness of 716.80 HV, a markedly improved polarisation resistance of 4011.2 Ω, and a considerably reduced corrosion rate of 0.21444 mm/year. Therefore, Improved mechanical and corrosion performance of Ti6Al4V matrix composites tends to reduce the weight of aerospace structures, improve fuel efficiency, and thereby enable the advancement of sustainable and benign aerospace technologies.